Econometrics of Estimating Causal Effects: An Overview for Social Work Researchers. (October 2015) - Lewis, Michael A.
Quantitative social work researchers are often interested in estimating the causal effects of various types of interventions. Randomized controlled trials (RCTs) are typically thought to be the "gold standard" when it comes to estimating such effects. RCTs, however, are sometimes neither ethical nor feasible, which means researchers will need alternatives if they're still interested in estimating causal effects. Economists have dealt with this issue as well and have developed econometric tools for estimating causal effects in the absence of data from RCTs. Many social work researchers may not be familiar with these methods, and the purpose of this article is to provide a "bird's eye" overview of them. Readers should obtain enough here to understand the issues involved in using these methods as well which ones might be useful for their research and, therefore, worth pursuing further.